2011
DOI: 10.1039/c1cp21429b
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of electrochemical oscillators with electrode size disparity: asymmetrical coupling and anomalous phase synchronization

Abstract: Experiments are carried out in dual electrode oscillatory Ni electrodissolution in which the two electrodes have different surface areas. The transition to phase synchronization is analyzed as asymmetrical coupling strength, induced by placing a cross resistance between the electrodes, is varied. It is shown that because of nonisochronicity (phase shear, i.e., strong dependence of period on amplitude) of the oscillators, anomalous phase synchronization effects can be observed: advanced/delayed synchronization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 67 publications
1
26
1
Order By: Relevance
“…For example, in pairs of asymmetrically coupled oscillators "anomalous" phase synchronization effects were reported in the form of advanced or delayed synchronization and frequency difference enhancement or inversion [25,27,30,31]; in globally coupled oscillators diffusion-induced inhomogeneity can occur in the form of periodic or quasiperiodic amplitude clusters [28]. In a previous work [32], by increasing the temperature of oscillatory Ni dissolution from 10 to 20 • C, nonisochronicity of asymmetrically coupled oscillators resulted in advanced or delayed synchronization depending on the relative frequencies of the driver and follower oscillators.…”
Section: Introductionmentioning
confidence: 95%
“…For example, in pairs of asymmetrically coupled oscillators "anomalous" phase synchronization effects were reported in the form of advanced or delayed synchronization and frequency difference enhancement or inversion [25,27,30,31]; in globally coupled oscillators diffusion-induced inhomogeneity can occur in the form of periodic or quasiperiodic amplitude clusters [28]. In a previous work [32], by increasing the temperature of oscillatory Ni dissolution from 10 to 20 • C, nonisochronicity of asymmetrically coupled oscillators resulted in advanced or delayed synchronization depending on the relative frequencies of the driver and follower oscillators.…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies with electrochemical systems [19,20,27] theoretical and experimental studies, it was demonstrated that such a reduced system could produce all the rich dynamics of the original network despite its simpler form.…”
Section: Star Network Of Coupled Bistable Lasersmentioning
confidence: 99%
“…These oscillators, detailed in Supplemental Material Sec. S3 [31] along with sample experimental trajectories, are described by m = 2 degrees of freedom, which represent the electrode potential and the concentration of the electroactive species in the vicinity of the electrode [32]. Unlike Stuart-Landau oscillators, the limit cycle in this case is not circular in the state space, and thus the phase is a complicated function that we will not attempt to describe analytically.…”
mentioning
confidence: 99%